Specific dermatoses of pregnancy - Ambros-Rudolph, C. M.; Sticherling, Michael (Hautarzt, 2017)
The specific dermatoses of pregnancy represent a heterogeneous group of inflammatory skin diseases related to pregnancy and/or the postpartum period. A clinically relevant classification has been well established over the past 10 years and includes pemphigoid gestationis, polymorphic eruption of pregnancy, intrahepatic cholestasis of pregnancy, and atopic eruption of pregnancy. The hallmark of all four entities is severe pruritus that is accompanied by characteristic skin changes. While some of these dermatoses are distressing only to the mother because of pruritus, others may be associated with significant fetal risks. Early diagnosis and prompt treatment are therefore essential. In this review, we discuss in detail pemphigoid gestationis, polymorphic and atopic eruptions of pregnancy whereas intrahepatic cholestasis of pregnancy is discussed in a separate article (Kremer A, Ständer S, DOI 10.1007/s00105-016-3923-y ). Furthermore, we present a helpful algorithm for diagnosis and management of pruritus in pregnancy.
EVALuna2:34362